ANALISIS STRUKTUR AKTANSIAL DAN FUNGSIONAL DALAM VOYAGE AU CENTRE DE LA TERRE KARYA JULES VERNE - Nirwana, Nirwana; Latjuba, Ade Yolanda; Armin, Mardi Adi (JURNAL ILMU BUDAYA, 2015)
This paper entitled "Structur actantial and functional analysis in the Voyage au center de la terre of awork of Jules Verne" which is one part of the thesis of the same title. The work of Verne is a sciencefiction novel that tells about the journey of a geologist Professor Lidenbrock with his nephew, Axel and ahunter whose they hired, Hans Bjelke, to look for the center of the earth. In this study, the selected theoryis from a structuralism of Algidras Julien Greimas which used as a theoretical basis.A.J.Greimas use actantial structural analysis and functional as the basic concept of his working steps.According to Greimas, actant is the smallest unit of narrative in the literary. Actants and personages arenot same; an actant may not manifest as a personage, but an abstract concept, a figure not lifeless,heirloom weapons or the like. In actantial structure, there are some buildings elements such as subject,object, sender, recipient, opponents, and helpers. Meanwhile, the functional structure is the simplificationof the functions in the story. Those functions comprised the initial situation, transformation, and the finalsituation. Transformation is divided into three stages, namely the proficiency test phase, the main phase,and the phase of glories. From actantial structure which arranged well, can then be determined a theme ofthis work.The results of the analysis, obtained five actantial structural and functional patterns. The five kinds ofpatterns starts from Prof. Lidenbrock began his journey looking for the center of the earth, until find thecenter of the earth; one of the patterns actantial structure and its functional is presented in this paper. Andof the five patterns it is also successfully determined the main theme of the novel, namely the spirit ofexploration..Key words : Actansial, Functional, Science-Fiction, Structuralism, A.J. Greimas